1993
DOI: 10.1037/h0078822
|View full text |Cite
|
Sign up to set email alerts
|

Episodically enhanced comprehension fluency.

Abstract: Fluent reading comprehension was explored in a series of experiments involving sentences presented in normal and inverted typography. Sentences read in a test phase had been read earlier in exactly the same form, or in versions that were created by (a) altering the word order within sentences to create randomly ordered word strings or (b) exchanging causally related clauses to form new meaningful sentences. Variation from exact repetition of word order or clause combination increased the time taken to read the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 58 publications
(99 reference statements)
3
17
0
Order By: Relevance
“…Consistent with the proposal by Carr et al (1989), it could be the activation or strengthening of lexical memory units. Alternatively, consistent with the findings of Levy et al (1993) and Masson (1993), the priming effects could depend on memory for specific conceptual processing components of the priming event, such as meaning comparison and decision.…”
Section: Repeated Semantic Comparisonssupporting
confidence: 58%
See 2 more Smart Citations
“…Consistent with the proposal by Carr et al (1989), it could be the activation or strengthening of lexical memory units. Alternatively, consistent with the findings of Levy et al (1993) and Masson (1993), the priming effects could depend on memory for specific conceptual processing components of the priming event, such as meaning comparison and decision.…”
Section: Repeated Semantic Comparisonssupporting
confidence: 58%
“…As described earlier, Carr et al (1989) concluded that priming effects in rereading text were due to activation of lexical memory units. However, this conclusion has been countered by evidence of priming effects associated with passage comprehension processes rather than individual word reading (Levy et al, 1993;Levy & Kirsner, 1989;Masson, 1993).…”
Section: Experiment·2mentioning
confidence: 94%
See 1 more Smart Citation
“…Reading two dissimilar texts should not lead to repetition effects because the second text cannot reinstate the episodic representation of the first text. Unlike abstract repetition effects, which are not based on memory for the text per se, episodic repetition effects are dependent on memory for the information in a text or the processes used to comprehend the text (Kolers, 1975(Kolers, , 1976Levy et al, 1995;Masson, 1995).…”
Section: Abstract Versus Episodic Models Of Text Repetition Effectsmentioning
confidence: 99%
“…There is a generally accepted explanation for this repetition effect: Memory of the text formed during the first reading facilitates processing during the second reading. There is, however, intense debate regarding why and how memory facilitates rereading (e.g., Bowers, 2000;Carlson, Alejano, & Carr, 1991;Carr, Brown, & Charalambous, 1989;Levy & Burns, 1990;Levy et al, 1995;Masson, 1995;Tenpenny, 1995). The debate has been centered on whether text repetition effects are based on abstract or episodic text representations and how the reader may use such representations.…”
mentioning
confidence: 99%